Secure Blockchain Based Data Storage and Integrity Auditing in Cloud - et. al., Sumathi M , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A blockchain is a linear collection of data elements, where each data element is called as block. All blocks are linked to form a chain and secured using cryptographic hash function. Each block typically contains a hash pointer as a link to a previous block, a timestamp and transaction data. Public verification techniques enable users to outsource the data integrity verification to a dedicated third party auditor. To ensure the security in the case that the auditor is compromised, the users are required to audit the auditor’s behaviors. Hence, the user data need to maintain in a secure way is an essential task along with data integrity. Blockchain provides such kind to secure data storage along with data integrity without compromising confidentiality. The double SHA provides a collision free secure storage than other technique. Hence Double SHA based block generation and verification is proposed in this work. In this work both data owner and public auditors are verified the integrity for providing highest accuracy. Experimental results show that the proposed technique provides better results and security to user data in an efficient manner is proved